EFEKTIFITAS PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 PADA MADRASAH IBTIDAIYAH - Nasrul Fauzi; Pertiwi Amalia Susanti (MISOOL: Jurnal Pendidikan Dasar, 2021)
This study aims to analyze: the effectiveness of online learning and the factors that influence its application at MI Al-Ikhtiar Al-Ma'arif 4, Sorong Regency. This study used a qualitative descriptive approach with six teachers and six students as informants. Collecting data using interview and observation techniques. The results of the study indicate that: the learning that is currently being carried out is less effective and there are still some obstacles. The perceived convenience is that learning can be done anywhere and it is considered that learning becomes more relaxed, the obstacles faced are the lack of readiness of students in receiving the material, the low concentration of students when learning takes place, and different student facilities so that online learning is not evenly distributed. Distance learning is considered less effective to be applied at the elementary school level considering that students cannot be left to carry out their own learning and must be guided, while parents have other activities.